2019
DOI: 10.1039/c9cp00735k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the quasi-planar B50boron cluster: topological path from B10and disk aromaticity

Abstract: The lowest-lying isomer of the B50 boron cluster is confirmed to have a quasi-planar shape with two hexagonal holes. This cluster is derived from a topological (leapfrog) path from B10 and its high thermodynamical stability is due to a disk aromaticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…A number of recent theoretical studies have revealed potentially interesting chemisorption properties of CO 2 on Boron-based clusters and related model solid surfaces [9][10][11][12][14][15][16]. Small Boron clusters, containing 13 or less atoms, have been shown both experimentally and theoretically to be planar or quasiplanar [17][18][19][20], while a number of medium size clusters (up to ∼ 40 atoms) are also expected to occur in planar-type structures on the basis of available experimental and/or theoretical studies [21][22][23][24][25]. Most of these clusters were produced using laser vaporization of a disk target [17,[21][22][23][24], and their corresponding photoemission [17,21,22,24] and infrared absorption spectra [23] were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent theoretical studies have revealed potentially interesting chemisorption properties of CO 2 on Boron-based clusters and related model solid surfaces [9][10][11][12][14][15][16]. Small Boron clusters, containing 13 or less atoms, have been shown both experimentally and theoretically to be planar or quasiplanar [17][18][19][20], while a number of medium size clusters (up to ∼ 40 atoms) are also expected to occur in planar-type structures on the basis of available experimental and/or theoretical studies [21][22][23][24][25]. Most of these clusters were produced using laser vaporization of a disk target [17,[21][22][23][24], and their corresponding photoemission [17,21,22,24] and infrared absorption spectra [23] were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular geometric configuration and attributes of pure 13 and doped boron clusters 49 have drawn much attention in recent years. The use of boron clusters as subunits in novel bioactive architectures with potential use as drugs is of primary importance 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The initial geometries of leapfrog B 24 clusters are built from a square and a rhombus following the scheme described for the making of B 50 by Pham et al [ 27 ] In this generating scheme, the omnicaping operation ( O ) adds an atom on the center of a square or rhombus, which is followed by a dual operation ( D ) that transforms face into vertex and vertex into hexagonal faces. Then, the resulting structure is reorganized by the action of a new operator consisting in the capping of new hexagons ( C ) and by an edge correction operation that tends to add one atom on each corner ( E ) in order to avoid empty space at the periphery.…”
Section: Methodsmentioning
confidence: 99%
“…The initial geometries of leapfrog B 24 clusters are built from a square and a rhombus following the scheme described for the making of B 50 by Pham et al [27] In this generating scheme, the omnicaping operation (O) adds an atom on the center of a square or rhombus, which is followed by a dual operation (D) that transforms face into vertex and vertex into hexagonal faces. Then, the resulting structure is The geometries of all B 24 clusters investigated in the present study are optimized using the M06-2X [34] and PBE [35] functionals with the 6- ) structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation